Body Shaming sebagai dampak standar kecantikan dalam film Imperfect - Juliana, Putri (Maliki Interdisciplinary Journal, 2024)
Body shaming has become one of the things that is popular on the Internet, generally this is widely interpreted as a negative behavior where someone tends to use it to criticize and ridicule someone's body shape. Actions of body shaming also occur a lot in the environment around us, the popularity of this phenomenon means that the issue of body shaming is often raised in the form of films, one of the films that raises the issue of body shaming is the 2019 film Imperfect, produced by Ernest Prakasa. By using John Fiske's semiotic studies, the researcher aims to find the meaning of body shaming which is often mentioned in this film, by using codes or signs in John Fiske's television semiotics by analyzing the level of reality or reality code in the film Imperfect. The method used in this research is descriptive qualitative. Researchers made observations and systematically recorded every dialogue that contained elements of body shaming in the imperfect film. By using John Fiske's semiotic studies to reveal that something shown in television media such as films or advertisements is a form of the existence of a reality, a fact that occurs in a social system (social reality), to reveal that reality is a product realized by humans or society itself. From the results of this analysis, researchers found 4 types of body shaming found in the imperfect film, namely fat shaming, skin shaming, face shaming, and hair shaming.